Abuela - Dorros, Arthur; Kleven, Elisa; Dorros, Sandra Marulanda (New York : Puffin Books, 1997)
While riding on a bus with her grandmother, a little girl imagines that they are carried up into the sky and fly over the sights of New York City.
Rosalba y su abuela realizan un extraordinario viaje volando en el aire, en la imaginacion de la niña, en correando el autobus.
Originally published: New York : Dutton Children's Books, c1995.
Accelerated Reader
Accelerated Reader AR
Keywords: Imagination -- Juvenile fiction; Flight -- Juvenile fiction; Grandmothers -- Juvenile fiction; Hispanic Americans -- Juvenile fiction; Imaginacion -- Novela juvenil; Vuelo -- Novela juvenil; Abuelas -- Novela juvenil; Hispanoestadounidenses -- Novela juvenil; New York (N.Y.) -- Juvenile fiction; Nueva York (Estados Unidos : Ciudad) -- Novela juvenil; #OwnVoices - Latinx